Bawwābāt al-Ma’ājim al-Raqmiyyah: Dirāsah Mu’jamiyah fī Dhau’i al-Lisāniyyāt al-Hasūbiyyah – al-Mu’jam al-Raqmī li Muśţalahāt al-Maktabāt wa al-Ma’lūmāt wa al-Arsyīf li Ahmad Muhammad al-Syamiy - Namūżajan (Digital Dictionaries Gates: A Lexical Study in the Light of Computational Linguistics - The Digital Dictionary of Library, Information and Archive Terms by Ahmed Mohamed Al-Shami - A Model ) - Iman Abdul Jaber Abdul Sami Allam; Soaad Tharwat Mohamed Nassef (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
تعنى هذه الورقة البحثية بدراسة نافذة جديدة من نوافذ اللسانيات الحاسوبية وهي : (بوابات المعاجم الرقمية ) وذلك من خلال دراسة بوابة (واجهة) المعجم الرقمي المختص (معجم الشامي). وقد تناول البحث دراسة في ثلاثة مباحث وهي تأصيل مصطلحات الدراسة، وبوابة المعجم الرقمي (مصطلحات المكتبات والمعلومات والأرشيف) لأحمد الشامي دراسة معجمية في ضوء اللسانيات الحاسوبية، والأخير روابط المعجم الرقمي لمصطلحات المكتبات والمعلومات والأرشيف دراسة معجمية حاسوبية. وقد اعتمد البحث على المنهج الوصفي التحليلي النقدي، من خلال وصف بوابة المعجم وتحليل البيانات الواردة فيها محاولة منا لتأصيل بعض قواعد المعجمية الحاسوبية، ومن ثم التطبيق على المعجم محل الدراسة لمعرفة مدى قبوليته معجميا، وكيف قامت بوابته بدورها معجميا من حيث التيسير على المستخدم، وإظهار مواطن الضعف الواردة فيها. وقد توصل البحث إلى العديد من النتائج من أهمها: أن البوابات الإلكترونية هي الواجهات أو المنافذ التي تُتيح لمستخدم الإنترنت خدماتها المتكاملة والولوجَ بسرعة وسهولة إلى أهم المواضيع، يصعب البحث عن معاني المصطلحات في هذا المعجم حيث إنه لا يوجد خانة منفردة لكتابة المصطلح المطلوب معناه، وعدم توفير واجهة رقمية تسمح للمستخدم بإضافة مصطلحات جديدة أو إيصال ملحوظة، واستخدام المعجم الروابط الإلكترونية للإحالة إلى موقع أو صورة أو للخروج من مصطلح إلى مصطلح آخر، كما أوصت الباحثتان بدراسة بوابات المعاجم الرقمية وعمل مقارنات بينها؛ لوضع ضوابط لبوابات تلك المعاجم. AbstractThis research paper is concerned with studying a new window of computational linguistics, which is: (digital dictionaries gates), through studying the portal (interface) of the specialized digital dictionary (Al-Shami dictionary). The research dealt with a study in three sections, which are the rooting of the study terms, and the digital lexicon portal (libraries, information and archive terms) by Ahmed Al-Shami, a lexical study in the light of computer linguistics, and the last links the digital lexicon of library, information and archive terms, a computer lexicographical study. The research relied on the descriptive, analytical and critical approach, by describing the lexicon portal and analyzing the data contained in it, in an attempt to establish some rules of computer lexicography, and then apply it to the lexicon under study to find out its lexical acceptability, and how its lexicographical role in terms of facilitating the user, showing weaknesses contained therein. The research has reached several results, the most important of which are: that electronic portals are the interfaces or ports that allow the Internet user its integrated services and access quickly and easily to the most important topics. Providing a digital interface that allows the user to add new terms or deliver a note, and use the dictionary electronic links to refer to a site or an image or to exit from one term to another term. The two researchers also recommended studying digital dictionaries portals and making comparisons between them; To set controls for the gates of those dictionaries.